Mapping Industrial Performance in Environmental Management in East Java Using Geographic Information Systems (GIS) - Serlly Frida Drastyana; Anif Prasetyorini; Mohammad Yusuf Setiawan; Diah Wijayanti Sutha; Puryanti; Silvia Catalan Ambag; Christine (JURNAL KESEHATAN LINGKUNGAN, 2026)
Introduction: Spatial analysis of industrial environmental performance data is necessary for optimizing industrial sites, mitigating environmental risks, enhancing environmental performance, minimizing adverse effects, and promoting industrial sustainability. This study aims to map the environmental performance of industry and its effect on water quality and the incidence of diarrhea in East Java Province, Indonesia. Methods: This research was observational and used secondary data. The population and sample of this study were all 38 districts and cities in East Java Province. The study was conducted from June to September 2025. This study utilized the Global Positioning System (GPS) to collect data, namely coordinate points based on the addresses of industries or companies in East Java. Coordinates were colored blue, green, or red according to the industrial environmental performance rating (PROPER). The data analysis in this study used linear regression and a spatial autocorrelation approach in ArcGIS. Results and Discussion: The data of performance in environmental management of companies for 2022–2023 for regencies or cities in East Java showed that the industries included in the PROPER assessment were mostly from Sidoarjo, Pasuruan, and Gresik. The red PROPER ratings were most prevalent in Gresik, Sidoarjo, and Surabaya, while the blue PROPER ratings were most prevalent in Pasuruan, Sidoarjo, and Gresik. Conclusion: There is a spatial effect on the distribution of the number of red proper in East Java province. And a significant correlation was found between the red PROPER rating and the number of diarrhea cases per district/city in East Java province.